The Prevalence of Ketogenic Diet among Adults with Chronic Disease in Saudi Arabia - Khalid Abdullah Algamdi,; Sajidah Hisham Abu Alsaud,; Ghada Badr Alghubaini,; Muna Mustafa Alsaggaf,; Ibtisam Ahmed Altalhi,; Jood Sami Asali,; Shada Mohammed Abyad,; Alzahrani, Khames T. (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Ketogenic diet was first approached diet in treatment of epilepsy in children, later on, many studies showed its positive effect on adults who have chronic diseases and obesity. The main aim of the diet is to allow the body to reach the state of ketosis by generating energy from fat rather than glucose, and this happen by lowering the carbohydrates, adding moderate protein and high fat, thus letting the body burn fat for fuel. Since more than 50 years studies linked consumption of saturated fat with cardio-metabolic disease risk and obesity, and nowadays many studies have shown a positive impact of consumption of saturated fat. Therefore, this is a study to determine the prevalence of Saudi adult with chronic disease who follow a ketogenic diet. Methods: This was an observational cross-sectional study based on web-survey questionnaires developed by developed originally by author with high confidence level. The sample size was 479 estimated using the Qualtrics calculator with a confidence level of 95% and a margin of error of 5%. The questionnaire is divided into four categories. We started the questioner with demographic factors including age, nationality, dental degree date and in which country, work setting and cariology course attendance. 2nd it was about 3 clinical scenarios. Data were collected using Google forms and prepared for analysis using Microsoft Excel. Statistical analysis was performed using the SPSS software. Results: The total number of the current study participants was 464, the highest percentage (33.90%) were in the age group of 40-50 years old, 44.80% were in the weight range of 61-80 kg, while 11.90% have a weight of >100 kg, and half (50%) of the participants have a height range of 151-160 cm. Most (71%) of the participants have a college educational level, and 44.30% were employees. The prevalence of hypercholesterolemia and diabetes among the respondents was 23.70%, and 2.50%, respectively. The overall prevalence of metabolic syndrome was 2.30%. Almost half (50.10%) of the participants reported having obesity, and 19.10% were hypertensive. Conclusion: Ketogenic diet in this review showed a positive results within the utilization in chronic illnesses and obesity. In any case, The long-term hazard related with adverse impacts is unknown; therefore, advance studies may be valuable. Future randomized clinical trials are required to affirm the viability of the ketogenic diet in different sorts of adults’ chronic illness and to supply advance data on a few uncertain commonsense issues, i.e., how long the ketogenic diet ought to be proceeded.